Sosialisasi Peran Artificial Intelligence Terhadap Proses Pembelajaran Mahasiswa Di Universitas Pelita Bangsa - Rifqi Putra Adhadi; Muhammad Rizky Efendi; Raka Muzakki; Hafizh Rizki Pratama Yudiansyah; Bintang Panjaitan; Rifqi Al-Muzaky (UNIB Press, 2024)
The rapid advancement of information technology greatly impacts education, especially in learning. Artificial Intelligence (AI) is pivotal in various sectors, including education. This study explores AI's role in student learning at Universitas Pelita Bangsa. AI adaptation addresses challenges like educator scarcity, offering tailored learning experiences. It fosters active engagement and immediate feedback. However, overreliance on AI may hinder creativity and change traditional teaching. A study was conducted at Universitas Pelita Bangsa, engaging 50 students through a Zoom seminar. Topics included AI introduction, educational applications, and pros and cons. Findings show high satisfaction (75% satisfied, 20% highly satisfied). Enhanced learning quality was observed. In conclusion, AI integration holds potential for better learning outcomes. Continuous evaluation and adaptability are vital. This study highlights the importance of student-centric approaches in AI integration.